Low self-esteem and psychiatric patients: Part I – The relationship between low self-esteem and psychiatric diagnosis - Silverstone, Peter H (BioMed Central, 2003)
BACKGROUND: The objective of the current study was to determine the prevalence and the degree of lowered self-esteem across the spectrum of psychiatric disorders. METHOD: The present study was carried out on a consecutive sample of 1,190 individuals attending an open-access psychiatric outpatient clinic. There were 957 psychiatric patients, 182 cases with conditions not attributable to a mental disorder, and 51 control subjects. Patients were diagnosed according to DSM III-R diagnostic criteria following detailed assessments. At screening, individuals completed two questionnaires to measure self-esteem, the Rosenberg self-esteem scale and the Janis and Field Social Adequacy scale. Statistical analyses were performed on the scores of the two self-esteem scales. RESULTS: The results of the present study demonstrate that all psychiatric patients suffer some degree of lowered self-esteem. Furthermore, the degree to which self-esteem was lowered differed among various diagnostic groups. Self-esteem was lowest in patients with major depressive disorder, eating disorders, and substance abuse. Also, there is evidence of cumulative effects of psychiatric disorders on self-esteem. Patients who had comorbid diagnoses, particularly when one of the diagnoses was depressive disorders, tended to show lower self-esteem. CONCLUSIONS: Based on both the previous literature, and the results from the current study, we propose that there is a vicious cycle between low self-esteem and onset of psychiatric disorders. Thus, low self-esteem increases the susceptibility for development of psychiatric disorders, and the presence of a psychiatric disorder, in turn, lowers self-esteem. Our findings suggest that this effect is more pronounced with certain psychiatric disorders, such as major depression and eating disorders.